Introduction to plant population - Silvertown, Jonathan W. (Blackwell Science, 2001)
This completely revised, fourth edition of Introduction to Plant Population Biology continues the approach taken by its highly successful predecessors. Ecological and genetic principles are introduced and theory is made accessible by clear, accurate exposition with plentiful examples. Models and theoretical arguments are developed gradually, requiring a minimum of mathematics.